"A joke a day keeps the doctor away?" Meta‐analytical evidence of differential associations of habitual humor styles with mental health. Issue 3 (12th February 2018) - Schneider, Martha; Voracek, Martin; Tran, Ulrich S.
Abstract : Humor and mental health are interconnected as is evidenced by a large number of studies. However, associations are only small and inconsistent as the operationalization of humor poses a methodological challenge. The Humor Styles Questionnaire (HSQ) differentiates four humor styles that might be beneficial or harmful to mental health. The aim of the present study was to meta‐analytically aggregate studies using the HSQ to assess the associations of different humor styles with four areas of mental health (self‐esteem, life satisfaction, optimism, depression). An extensive electronic database literature search identified 37 studies that reported correlations between the HSQ scales and the four areas of mental health in 45 independent samples (total N = 12, 734). In total, 16 meta‐analyses were conducted. Moderating effects of participant age, sex, and geographic region were examined via subgroup analyses and meta‐regression. Humor styles differed in terms of their associations with mental health. Health‐promoting humor styles were overall positively correlated with mental health (small‐to‐medium effect sizes). Self‐defeating humor was overall negatively correlated with mental health. Aggressive humor was overall unrelated with mental health. Moderator analyses suggested geographic differences (Eastern vs. Western samples) and sex differences for some of these associations. Fostering specific humor styles may be beneficial for mental health. In addition, observing the habitual use of humor styles might help therapists to develop a better understanding of their clients. Differences in the utilization and the correlates of humor styles in Eastern and Western societies, and sex differences, need to be addressed in future research.